Radical Environmentalism and “commoning”: synergies between ecosystem regeneration and social governance at Tamera Ecovillage, Portugal - Esteves, A. M. (Antipode, 2017)
This article explores the scope and limitations of Radical Environmentalism as a source of practices of “commoning”. The application of the radical environmental “Healing Biotope” model in Tamera, an ecovillage located in southern Portugal, further expands the understanding of “commoning” as a social process, as well as of Radical Environmentalism as a cognitive framework. This article distinguishes between the technical and political dimensions of “commoning”. It also identifies two structuring dimensions of Radical Environmentalism, hereby called integrative rationality and the experiential action research and learning methodology. These dimensions support the technical aspect of “commoning” in Tamera by promoting epistemic and methodological coherence between social and environmental technologies. Despite their contested scientific validity, they contribute to the sustainability of the project by promoting synergies between ecological regeneration and social governance. However, they have limited capacity to address the political dimension of “commoning”, related with rank and socio-economic inequalities among members.